Integrating E-Leanrning and Digital Assessment in Indonesian Maritime Vocational Education: Enhancing Work Readiness - Toko, Gigih Prastyan; Cahyadi, Tri; Robbany, Inayatur; Ridwan, Mohamad (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This qualitative study investigates the integration of E-learning and Digital Assessment at STIP Jakarta and its impact on the work readiness of Diploma-IV cadets, aligned with international STCW competency standards. Through in-depth interviews and focus group discussions with 70 final-year cadets, the research reveals a dualistic outcome: while digital tools are highly effective in delivering theoretical knowledge and developing simulator-based operational skills, they exhibit significant limitations in fostering hands-on practical abilities and essential psychosocial competencies such as leadership and mental resilience. The findings identify a critical